Effects of dietary water spinach supplementation on the meat quality attributes of local geese in Bangladesh - Sarker, Md Sazedul Karim; Ety, Most Umme Saleheen; Rana, Md Masud; Sharmin, F; Khatun, H; Lisa, Nusrat Nourin; Faruque, S; Zihan, S S; Islam, Aminul (Bangladesh Journal of Livestock Research, 2025)
Since geese (Anser anser) are herbivorous waterfowl, their gizzards are larger and stronger, Allowing them to break down high-fiber roughages with greater force and consume enormous volumes of forages. The goal of this study was to evaluate the effectiveness of water spinach (Ipomoea aquatica) in identifying the water-holding capacity, meat nutrient composition, pH, drip loss, cooking loss, slaughter and carcass characteristics and meat colour of local Bangladeshi white and grey geese varieties supplemented with varying amounts of water spinach. A semi-intensive production system was used to raise 36 adult geese of both white and grey kinds, which were slaughtered at 28 weeks of age. They were split into four groups at random, each consisting of three replicates with three geese each. Maize soya-based diet was considered as control diet (CL) (2700ME/Kcal, 16% CP) where T1 & T3 group were given 180g of CL diets in white and grey variety respectively and other diets included T2 (White variety)-80g of water spinach + 140g of CL diet, T4 (Grey variety)- 80g of water spinach + 140g of CL diet. Following rearing, each bird was weighed separately. Treatments significantly affected the redness value (a*) (p < 0.05). A statistical analysis was performed on 12 slaughter traits, which were separated into two groups: measured traits and calculated traits. For slaughter traits, results suggested that beneficial trails were not significantly varied but tented to be higher in the supplemented group. pH value for T3 group was higher than other groups. Additionally, supplemented group showed lowest drip loss and cooking loss and best water holding capacity, but these parameters were not significantly veried. Notably, the supplemented groups had exhibited the highest dressing percentage, desirable slaughter and carcass traits as well as favourable meat quality parameters. Taking these factors into account, we can say that adding water spinach to geese improved their slaughter and carcass characteristics, meat colour, pH, drip loss, cooking loss, water-holding capacity and meat nutritional content. Bang. J. Livs. Res. Vol. 30 (1&2), 2023: P. 23-35